SCHOOL LEADERSHIP LEADERSHIP IN DEVELOPING A LEADING PROGRAM IN SMA MTA SURAKARTA - Datik Nurmuslimah; Istanto Istanto (Universitas Muhammadiyah Surakarta, 2018)
Principal Leadership is how school principals lead to be able to influence all school members to achieve quality schools. Principal leadership as a manager in developing special class programs at MTA Surakarta High School by doing planning, organizing, mobilizing, and monitoring. Whereas the style used by the Principal in developing special class programs is a collaborative style, a combination of visionary style and democratic style.The purpose of this study is to describe the principal's leadership in developing a Special Class Program in Surakarta MTA High School 2018/2019 Academic Year, describing the principal's leadership style in developing Special Class Programs in Surakarta MTA High School 2018/2019 Academic Year.This study took place in MTA Surakarta High School. Data collection techniques using interview methods, observation methods, and documentation methods. Data analysis was carried out through four stages, including: data collection, data reduction, data presentation, and conclusion. The data validity test uses data triangulation which is to re-inquire the main subject statement to the supporting source to find out whether it is true or not.The results of this study are (1) Principal leadership in MTA Surakarta High School as a manager especially in developing special class programs is to establish good cooperative relations with partner institutions, namely Tahfidz with teachers who are already hafidz, Arabic Language in collaboration with Ma'had Abu Bakr, and English in collaboration with IEC. The principal in collaboration with the curriculum divides the lesson schedule in the special class program with the format of half the number of students in the class taking regular lessons, half of them taking tahfidz lessons. The headmaster always invites discussion of teachers who teach special class programs for better development. The principal conducts meetings both jointly and individually in accordance with the necessary interests. The principal is always trying to follow all educational activities. The principal always gives motivation to teachers, staff / employees, and students. (2) Principal leadership style in developing special class programs using collaborative styles, namely the visionary style and democratic style. This means that principals provide motivation that is always associated with death, listen to all criticisms and suggestions from school members and stakeholders, respect the ideas and creativity of school people, always act decisively towards policies that have been made, always try to be fair to every problem.